Durable super-hydrophobic composite filler, preparation method and application thereof, durable super-hydrophobic composite coating and coating

By growing micro-nano two-particle silica particles in situ on the surface of hydroxylated boron nitride, durable superhydrophobic composite filler is prepared, which solves the problems of poor mechanical durability and environmental pollution of the existing coatings, and achieves long-term application of efficient and environmentally friendly superhydrophobic coatings.

CN120118557APending Publication Date: 2025-06-10WUHAN INST OF TECH

Patent Information

Application Number
CN202510275598.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings have poor mechanical durability and are difficult to achieve long-term durability applications. At the same time, many methods and processes are complex or require the addition of fluorine elements that cause environmental pollution.

Method used

Micro-nano two-particle silica particles are grown in situ by performing a two-step reaction method on the surface of hydroxylated boron nitride to form a durable superhydrophobic composite filler with covalent bonding, which is used to prepare coatings with superhydrophobicity and mechanical durability.

Benefits of technology

It realizes the long-term application of superhydrophobic coatings, has excellent mechanical durability and environmental protection performance, and avoids the use of fluorine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005304114930000091
    Figure BDA0005304114930000091
  • Figure HDA0005304114950000011
    Figure HDA0005304114950000011
  • Figure HDA0005304114950000012
    Figure HDA0005304114950000012
Patent Text Reader

Abstract

The invention discloses a durable super-hydrophobic composite filler, a preparation method and application thereof, a durable super-hydrophobic composite coating and a coating, and belongs to the technical field of composite micro-nano coatings. The preparation method comprises the following steps: 1) dispersing hydroxylated boron nitride particles with a first solvent, adding acid to adjust the particles to be acidic, then adding a silicon source, and growing micron-sized SiO2 on the surface of hydroxylated boron nitride in situ to obtain first-grade BN-coated SiO2 composite particles; and 2) dispersing the primary BN-coated SiO2 composite particles by a second solvent, adding alkali to adjust the primary BN-coated SiO2 composite particles to be alkaline, then adding a silicon source and a modifier, and growing nanoscale SiO2 on the surfaces of the primary BN-coated SiO2 composite particles in situ to obtain the durable super-hydrophobic composite filler. A super-hydrophobic coating prepared by applying the durable super-hydrophobic composite filler to a coating has the advantages of high mechanical property and excellent durability, the preparation process is simple and environment-friendly, and the preparation and application of the environment-friendly, large-scale and large-area super-hydrophobic coating are expected to be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite micro-nano coating, and particularly relates to a durable superhydrophobic composite filler, a preparation method and application thereof, a durable superhydrophobic composite coating and a coating. Background Art

[0002] Ice formation and icing on various exposed surfaces are common and inevitable phenomena. When severe, they will affect people's normal life, have an adverse impact on industrial production, and even cause serious disasters and economic losses. For example, ice formation on the blades of wind turbines increases the weight of the blades, causing the body to lose balance and collapse; icing on high-voltage transmission lines affects normal power supply; icing on aircraft engines and wings causes flight accidents; icing on high-speed rail power supply lines affects normal transportation; icing on the body or the bottom of the train during its running in cold regions leads to the train getting out of control and derailing, resulting in major traffic accidents. Traditional de-icing methods, such as mechanical, electrical, chemical methods, etc., have problems such as low efficiency, high energy consumption, and easy to cause secondary pollution to the environment, so they are limited in practical applications. Superhydrophobic surfaces are bionic technologies based on the "lotus effect". The special surfaces formed by the combined action of micro-nano structures and low surface energy substances can reduce the icing temperature, delay the icing speed, reduce the adhesion strength of the attached ice, and promote the rolling of droplets, achieving an efficient anti-icing effect.

[0003] In addition, metals and their alloys play a crucial role in the engineering field due to their unique properties, but they are easily corroded in humid environments, which limits their long-term applications. Since the micro-nano structures on the surface of superhydrophobic coatings can seal a large amount of air, when metals and their alloys are coated with superhydrophobic coatings, the air cavities formed on the surface significantly reduce the actual contact area between the metal and its alloy matrix and the corrosive medium, thereby enabling efficient corrosion protection of metals. Therefore, superhydrophobic coatings have outstanding anti-corrosion effects on metal surfaces.

[0004] In recent years, the research on superhydrophobic coatings has been gradually deepened. Chinese Patent CN105602297A obtains a superhydrophobic composite particle dispersion with a superhydrophobic composite particle size by simply mixing nanoparticles with average particle sizes of 100 - 300 nm, 20 - 50 nm, and 5 - 10 nm in a dispersion liquid and modifying them with a silane coupling agent under the action of a catalyst. Then, by applying it to a substrate, a superhydrophobic coating with a water contact angle > 160° and a rolling angle < 5° can be obtained. However, its wear resistance needs to be improved, and it is difficult to achieve long-term and durable applications. Another example is Chinese Patent CN109135565A, which prepares a superhydrophobic coating by using a fluorosilicone resin as a binder and combining silica with two particle sizes (500 nm silica and 15 nm silica). However, the particle dispersion achieved only by blending has weak intermolecular forces after film formation, and it is very easy to have a situation of dot-like dropping, affecting its long-term and durable hydrophobic performance. At the same time, this method introduces fluorine elements that are not friendly to the environment and is prone to causing environmental pollution. Chinese Patent CN108299827A prepares a stainless steel mesh coated with SiO 2 nanoparticle suspension to prepare a stainless steel mesh coated with SiO 2 nanoparticles. Press it onto the surface of a PDMS substrate and remove the stainless steel mesh after curing to obtain a durable PDMS superhydrophobic film. However, the preparation process requires secondary film pressing, which limits the large-scale and large-area preparation.

[0005] In summary, it can be seen that there are not few preparation methods for superhydrophobic coatings at present. However, the vast majority of the schemes have complex processes or need to add fluorine elements that cause potential pollution to the environment. And due to the limitation of the wear resistance of the coating, long-term applications cannot be achieved, and it is difficult to meet the requirements of durability in industry. Summary of the Invention

[0006] The purpose of the present invention is to provide a durable superhydrophobic composite filler, its preparation method and application, a durable superhydrophobic composite coating and a coating. The superhydrophobic coating prepared by using this composite filler in the coating has good mechanical properties and excellent durability, making up for the defects of poor mechanical durability and high fluorine content in the existing superhydrophobic coatings, and providing technical support for the long-term and durable use of superhydrophobic coatings.

[0007] To solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0008] Provide a preparation method of a durable superhydrophobic composite filler, including the following steps:

[0009] 1) After dispersing hydroxylated boron nitride particles in a first solvent, adjust the pH to acidic with an acid, and then add a silicon source to carry out the first composite reaction to in-situ grow micron-sized SiO 2 on the surface of hydroxylated boron nitride to obtain first-stage BN@SiO 2 composite particles;

[0010] 2) Disperse the primary BN@SiO composite particles obtained in step 1) with a second solvent, adjust the pH to alkaline with an alkali, then add a silicon source and a modifier, and carry out a second composite reaction to in-situ grow nano-scale SiO on the surface of the primary BN@SiO composite particles. 2 After dispersion, add an alkali to adjust to alkaline, then add a silicon source and a modifier, and carry out a second composite reaction to in-situ grow nano-scale SiO on the surface of the primary BN@SiO composite particles. 2 on the surface of the composite particles to obtain secondary BN@SiO composite particles, which are the durable superhydrophobic composite filler. 2 composite particles, which are the durable superhydrophobic composite filler. 2 According to the above scheme, in step 1), the reaction conditions are: the temperature is 20 - 80 °C, and the time is 1 - 3 h.

[0011] According to the above scheme, in step 1), after the reaction, centrifuge to separate and remove the supernatant, wash the obtained solid precipitate with water until the supernatant is neutral, and dry to obtain the primary BN@SiO composite particles.

[0012] According to the above scheme, in step 1), after the reaction, centrifuge to separate and remove the supernatant, wash the obtained solid precipitate with water until the supernatant is neutral, and dry to obtain the primary BN@SiO composite particles. 2 composite particles.

[0013] According to the above scheme, in steps 1) and 2), the first solvent and the second solvent are independently selected from at least one or a mixture of several of methanol, ethanol, propanol, isopropanol, and toluene; preferably, the mass ratio of the hydroxylated boron nitride particles to the first solvent is (0.001 - 0.05):1, more preferably (0.005 - 0.03):1; the mass ratio of the primary BN@SiO composite particles to the second solvent is (0.001 - 0.05):1, more preferably (0.005 - 0.03):1. 2 composite particles to the second solvent is (0.001 - 0.05):1, more preferably (0.005 - 0.03):1.

[0014] According to the above scheme, in steps 1) and 2), the silicon source is independently selected from at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, and sodium silicate; preferably, the silicon source is sodium silicate and it is prepared into a solution with a mass fraction of 3 - 10% and added; more preferably, the modulus of sodium silicate is 1.5 - 3.5.

[0015] According to the above scheme, in step 1), the acid is sulfuric acid with a mass fraction of 0.5 - 39%.

[0016] According to the above scheme, in step 1), the particle size of the hydroxylated boron nitride is 8 - 15 μm, preferably 10 - 13 μm.

[0017] According to the above scheme, in step 1), the weight ratio of the hydroxylated boron nitride to the silicon source is (1 - 3):1, preferably (1.5 - 2.5):1.

[0018] According to the above scheme, in step 1), adjusting the pH to acidic means the pH is 3.5 - 5.5; preferably, pH = 4 - 5.

[0019] According to the above solution, in step 2), the reaction conditions are as follows: the temperature is 20 - 80 °C, and the time is 1 - 3 h.

[0020] According to the above solution, in step 2), after the reaction, centrifugation is carried out to remove the supernatant. The obtained solid precipitate is washed with water until the supernatant is neutral, and then dried to obtain secondary BN@SiO 2 composite particles.

[0021] According to the above solution, in step 2), the weight ratio of the primary BN@SiO 2 composite particles to the silicon source is (1 - 5):1, preferably (1.5 - 4):1. The weight ratio of the primary BN@SiO 2 composite particles to the modifier is (0.5 - 3):1, preferably (1 - 2):1.

[0022] According to the above solution, in step 2), adjusting to alkaline by adding alkali means the pH is 8 - 10.5. Preferably, the pH = 8.5 - 9.5.

[0023] According to the above solution, in step 2), the alkali is ammonia water with a mass fraction of 0.5 - 25%.

[0024] According to the above solution, in step 2), the modifier is at least one or a mixture of several of octyltrimethoxysilane, octyltriethoxysilane, octyltrichlorosilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, dodecyltrichlorosilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and hexadecyltrichlorosilane.

[0025] Provide a durable superhydrophobic composite filler prepared by the above preparation method.

[0026] Provide an application of the above durable superhydrophobic composite filler in a durable superhydrophobic composite coating.

[0027] Provide a durable superhydrophobic composite coating comprising the above durable superhydrophobic composite filler.

[0028] According to the above solution, the durable superhydrophobic composite coating includes the above durable superhydrophobic composite filler, resin, curing agent, third solvent, and additives; wherein:

[0029] The weight ratio of the additives, curing agent, and durable superhydrophobic composite filler to the resin is (0.01 - 0.15):(0.01 - 0.5):(0.01 - 0.5):1; the weight ratio of the resin to the third solvent is (0.005 - 0.5):1;

[0030] The additives include a defoaming agent and a leveling agent.

[0031] Preferably, the resin is one or more of E12 epoxy resin, E42 epoxy resin, E44 epoxy resin, and E51 epoxy resin; more preferably, at least one of E44 and E51 epoxy resins.

[0032] Preferably, the curing agent is at least one of diethylenetriamine, triethylenetetramine, diaminodiphenylmethane, m-phenylenediamine, and dicyandiamide.

[0033] Preferably, the third solvent is at least one or a mixture of several of ethyl acetate, toluene, xylene, butyl acetate, tetrahydrofuran, ethanol, cyclohexane, and acetone.

[0034] Preferably, the defoaming agent is selected from one or more of polydimethylsiloxane defoaming agents, ethylene glycol siloxane defoaming agents, and polyether defoaming agents; the leveling agent is selected from at least one of polydimethylsiloxane leveling agents, organically modified polydimethylsiloxane leveling agents, and polymethylphenylsiloxane leveling agents.

[0035] Preferably, the weight ratio of the defoaming agent to the leveling agent is (0.5 - 3):1.

[0036] Preferably, the weight ratio of the curing agent to the resin is (0.1 - 0.3):1; the weight ratio of the durable superhydrophobic composite filler to the resin is (0.1 - 0.3):1; the weight ratio of the resin to the third solvent is (0.01 - 0.5):1.

[0037] Preferably, the durable superhydrophobic composite coating is dispersed by ultrasonic dispersion or high-speed shear dispersion. More preferably, the ultrasonic time is 5 - 60 min; the rotation speed is 200 - 1500 r / min, and the time is 0.5 - 3 h.

[0038] A durable superhydrophobic composite coating is provided, which is prepared by coating the above-mentioned durable superhydrophobic composite coating on a substrate and then heating and curing.

[0039] According to the above scheme, the coating thickness is 1 - 500 μm.

[0040] According to the above scheme, the static angle range of the coating is 151° - 169°, and the dynamic angle range is 4° - 9.5°.

[0041] According to the above scheme, the friction cycle number of the coating is 190 - 220 times.

[0042] According to the above scheme, the adhesion level range of the coating is 4B - 5B.

[0043] According to the above scheme, the coating process is: scraping coating, spin coating, spraying, or dip coating.

[0044] According to the above scheme, the heat curing process is: the temperature range is 25 - 120 °C, and the time range is 0.5 - 24 h.

[0045] According to the above scheme, the substrate includes a non-metallic substrate and a metal substrate; the non-metallic substrate is selected from a glass plate, a PE plate or a silicone rubber plate, and the metal substrate is selected from a copper plate, an aluminum plate or an iron plate.

[0046] According to the above scheme, the substrate is pretreated, and the pretreatment steps include: subjecting the substrate to a first ultrasonic treatment using acetone, subjecting the substrate to a second ultrasonic treatment using deionized water, and then performing a drying treatment; the conditions for the first ultrasonic treatment include: a temperature of room temperature and a time of 5 to 25 minutes; the conditions for the second ultrasonic treatment include: a temperature of room temperature and a time of 5 to 25 minutes. The drying treatment adopts high-purity nitrogen blowing or oven drying.

[0047] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:

[0048] 1. The present invention provides a method for preparing a durable super-hydrophobic composite filler, wherein micro-nano double-particle size silica particles are in situ grown on the surface of hydroxylated boron nitride by a two-step reaction method to form a durable super-hydrophobic composite filler with covalent bond; the filler is used in a coating to prepare a super-durable super-hydrophobic coating, so that the coating has super-hydrophobicity and mechanical durability; wherein: on the one hand, the lubrication characteristics of the two-dimensional structure of boron nitride reduce the friction coefficient of the coating and enhance wear resistance, while the super-strong binding force between boron nitride and the micro-nano particles grown in situ on its surface can prevent wear and further improve wear resistance; on the other hand, the two-step combination method allows micro-nano particles to grow uniformly on the surface of boron nitride, and the synergistic structure of the double-particle hierarchical arrangement overcomes the defect that the hydrophobic performance of the micro-micron particles or nano-nano particles deposited in traditional blending is easily invalid after wear, and at the same time, the micron particle silica can further protect the nano silica from completely destroying the surface roughness during deep wear; under multiple effects, the prepared coating has strong mechanical properties, can achieve long-term application of the super-hydrophobic coating, and has a wide range of application prospects.

[0049] 2. The composite filler preparation method provided by the present invention has simple process, fluorine-free raw materials and solvents, is environmentally friendly, has low preparation cost, and mild reaction conditions. After the composite filler is used in the coating, it can be directly coated on the substrate to achieve a long-lasting and durable super-hydrophobic effect of the coating, and is expected to realize the preparation and application of environmentally friendly, large-scale, and large-area super-hydrophobic coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0051] Figure 1 The preparation process of a durable super-hydrophobic composite coating is shown in the example.

[0052] Figure 2 The figure shows the wear resistance mechanisms of a conventional superhydrophobic coating and the durable superhydrophobic composite coating prepared in the examples of the present invention. Among them, Figure a is a schematic diagram showing that the superhydrophobic performance of the conventional superhydrophobic coating is prone to failure after wear; Figure b is a mechanism diagram of the boron nitride layered structure in the durable superhydrophobic composite coating of the present invention resisting wear and preventing the failure of superhydrophobic performance; Figure c is a mechanism diagram of the micron-sized silica particles further protecting the nano-sized silica particles to prevent the failure of superhydrophobic performance when the durable superhydrophobic composite coating of the present invention is deeply worn.

[0053] Figure 3 It is a schematic diagram of the water contact angle of the superhydrophobic composite coating in Example 1.

[0054] Figure 4 It is a schematic diagram of the water contact angle of the superhydrophobic composite coating in Example 1 after 200 cycles of friction.

[0055] Figure 5 It is a schematic diagram of the water repellency of the superhydrophobic composite coating in Example 1 after being scratched with a cross cutter and peeled off with tape. Detailed implementation manners

[0056] In order to be able to more clearly understand the technical means of the present invention and implement it in accordance with the content of the specification, and in order to make the above and other purposes, features and advantages of the present invention more obvious and understandable, the following will be described in detail with specific examples:

[0057] The substrate in the following examples is an iron plate, and the iron plate is first pretreated. Specifically: the iron plate is subjected to the first ultrasonic treatment with acetone for 10 minutes; then subjected to the second ultrasonic treatment with deionized water for 10 minutes; finally placed in an 80°C drying oven for drying treatment for 15 minutes.

[0058] Example 1

[0059] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0060] (1) Disperse 1 g of hydroxylated boron nitride particles (10 - 13 μm) in 100 g of ethanol, add sulfuric acid (mass fraction 20%) to adjust its pH = 4, slowly dropwise add 5 g of an aqueous solution of 10% sodium silicate (modulus 3.1 - 3.4) for reaction, the reaction temperature is 20°C, the reaction time is 2 h, after the reaction is completed, centrifuge to separate and remove the supernatant, and wash the obtained solid precipitate with water until the supernatant is neutral, and obtain primary BN@SiO 2 composite particles, where SiO 2 is in micron size.

[0061] (2) Take 1 g of the primary BN@SiO obtained in step (1) 2Composite particles are dispersed in 100 g of toluene, and ammonia water (mass fraction 13%) is added to adjust its pH = 8. 5 g of an aqueous solution of sodium silicate (modulus 3.1 - 3.4) with a concentration of 5% is slowly added dropwise, and 0.5 g of cetyltrimethoxysilane is added. The reaction temperature is 40 °C, the reaction time is 2 h. After the reaction is completed, the supernatant is removed by centrifugation, and the obtained solid precipitate is washed with water until the supernatant is neutral, and dried to obtain secondary BN@SiO 2 composite particles, where SiO 2 is of nanoscale size.

[0062] (3) 0.5 g of the secondary BN@SiO 2 composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent are mixed and ultrasonically mixed for 30 min to obtain a coating.

[0063] (4) The coating is evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20 - μm coating.

[0064] Example 2

[0065] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0066] (1) 1 g of hydroxylated boron nitride particles (10 - 13 μm) are dispersed in 100 g of ethanol, and sulfuric acid (mass fraction 20%) is added to adjust its pH = 4. 5 g of an aqueous solution of sodium silicate (modulus 3.1 - 3.4) with a concentration of 10% is slowly added dropwise for reaction. The reaction temperature is 20 °C, the reaction time is 2 h. After the reaction is completed, the supernatant is removed by centrifugation, and the obtained solid precipitate is washed with water until the supernatant is neutral, and dried to obtain primary BN@SiO 2 composite particles, where SiO 2 is of micron - scale size.

[0067] (2) The 1 g of primary BN@SiO 2 composite particles obtained in step (1) are dispersed in 100 g of toluene, and ammonia water (mass fraction 13%) is added to adjust its pH = 9.5. 5 g of an aqueous solution of sodium silicate (modulus 3.1 - 3.4) with a concentration of 5% is slowly added dropwise, and 0.5 g of dodecyltrimethoxysilane is added. The reaction temperature is 40 °C, the reaction time is 2 h. After the reaction is completed, the supernatant is removed by centrifugation, and the obtained solid precipitate is washed with water until the supernatant is neutral, and dried to obtain secondary BN@SiO 2 composite particles, where SiO 2 is of nanoscale size.

[0068] (3) 0.5 g of the secondary BN@SiO 2Composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent were mixed and ultrasonically mixed for 30 min to obtain a coating.

[0069] (4) The coating was evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20-μm coating.

[0070] Example 3

[0071] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0072] (1) 1 g of hydroxylated boron nitride particles (10 - 13 μm) was dispersed in 100 g of ethanol, sulfuric acid (mass fraction 20%) was added to adjust its pH = 5, 5 g of a 10% sodium silicate (modulus 3.1 - 3.4) aqueous solution was slowly added dropwise, the reaction temperature was 20 °C, the reaction time was 2 h, after the reaction was completed, the supernatant was removed by centrifugation, and the obtained solid precipitate was washed with water until the supernatant was neutral, and dried to obtain primary BN@SiO 2 composite particles, where SiO 2 is in the micron size.

[0073] (2) 1 g of primary BN@SiO 2 composite particles was dispersed in 100 g of toluene, ammonia water (mass fraction 13%) was added to adjust its pH = 8, 5 g of a 5% sodium silicate (modulus 3.1 - 3.4) aqueous solution was slowly added dropwise, 0.5 g of cetyltrimethoxysilane was added, the reaction temperature was 40 °C, the reaction time was 2 h, after the reaction was completed, the supernatant was removed by centrifugation, and the obtained solid precipitate was washed with water until the supernatant was neutral, and dried to obtain secondary BN@SiO 2 composite particles, where SiO 2 is in the nano size.

[0074] (3) 0.5 g of secondary BN@SiO 2 composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent were mixed and ultrasonically mixed for 30 min to obtain a coating.

[0075] (4) The coating was evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20-μm coating.

[0076] Example 4

[0077] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0078] (1) Dispersed 1 g of hydroxylated boron nitride particles (10 - 13 μm) in 100 g of ethanol, added sulfuric acid (mass fraction 20%) to adjust its pH = 5, slowly dropped 5 g of a 10% sodium silicate (modulus 3.1 - 3.4) aqueous solution for reaction, the reaction temperature was 20 °C, the reaction time was 2 h. After the reaction was completed, centrifuged to separate and remove the supernatant, the obtained solid precipitate was washed with water until the supernatant was neutral, and dried to obtain primary BN@SiO 2 composite particles, where SiO 2 is in micron size.

[0079] (2) Dispersed 1 g of the primary BN@SiO 2 composite particles in 100 g of toluene, added ammonia water (mass fraction 13%) to adjust its pH = 9.5, slowly dropped 5 g of a 5% sodium silicate (modulus 3.1 - 3.4) aqueous solution, added 0.5 g of dodecyltrimethoxysilane, the reaction temperature was 40 °C, the reaction time was 2 h. After the reaction was completed, centrifuged to separate and remove the supernatant, the obtained solid precipitate was washed with water until the supernatant was neutral, and dried to obtain secondary BN@SiO 2 composite particles, where SiO 2 is in nano size.

[0080] (3) Mixed 0.5 g of the secondary BN@SiO 2 composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of xylene, 0.1 g of polydimethylsiloxane defoamer, 0.1 g of organically modified polydimethylsiloxane leveling agent, and ultrasonically mixed for 30 min to fully mix, obtaining a coating.

[0081] (4) Sprayed the coating evenly on an iron plate, heated at 80 °C for 60 min for curing, obtaining a 20 - μm coating.

[0082] Comparative Example 1

[0083] Provided a preparation method of a durable superhydrophobic composite coating, including the following steps:

[0084] (1) Dispersed 1 g of hydroxylated boron nitride particles (10 - 13 μm) in 100 g of ethanol, added sulfuric acid (mass fraction 20%) to adjust its pH = 5, slowly dropped 5 g of a 10% sodium silicate (modulus 3.1 - 3.4) aqueous solution, the reaction temperature was 20 °C, the reaction time was 2 h. After the reaction was completed, centrifuged to separate and remove the supernatant, the obtained solid precipitate was washed with water until the supernatant was neutral, and dried to obtain primary BN@SiO 2 composite particles, where SiO 2 is in micron size.

[0085] (2) 0.5 g of first-grade BN@m-SiO₂ composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent were mixed and ultrasonically mixed for 30 min to obtain a coating.

[0086] (3) The coating was evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20-μm coating.

[0087] Comparative Example 2

[0088] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0089] (1) 1 g of hydroxylated boron nitride particles (10 - 13 μm) was dispersed in 100 g of toluene, and ammonia water (mass fraction 13%) was added to adjust its pH = 9.5. 5 g of an aqueous solution of 5% sodium silicate (modulus 3.1 - 3.4) was slowly added dropwise, and 0.5 g of dodecyltrimethoxysilane was added. The reaction temperature was 20 °C, and the reaction time was 2 h. After the reaction was completed, the supernatant was removed by centrifugation, and the obtained solid precipitate was washed with water until the supernatant was neutral and dried to obtain BN@nSiO 2 composite particles, where SiO 2 is of nanoscale size.

[0090] (2) 0.5 g of BN@n-SiO 2 composite particles, 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent were mixed and ultrasonically mixed for 30 min to obtain a coating.

[0091] (3) The coating was evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20-μm coating.

[0092] Comparative Example 3

[0093] A method for preparing a durable superhydrophobic composite coating is provided, including the following steps:

[0094] (1) 0.5 g of hydroxylated boron nitride (10 - 13 μm), 2.5 g of epoxy E44 resin, 0.25 g of diethylenetriamine, 20 g of ethyl acetate, 0.1 g of polydimethylsiloxane defoamer, and 0.1 g of organically modified polydimethylsiloxane leveling agent were mixed and ultrasonically mixed for 30 min to obtain a coating.

[0095] (2) The coating was evenly sprayed on an iron plate and cured by heating at 80 °C for 60 min to obtain a 20-μm coating.

[0096] The parameters such as the particle size of micron silica, the particle size of nano silica, the static contact angle, the dynamic contact angle, the number of friction cycles, and the adhesion force of the coatings obtained in Test Examples 1-4 and Comparative Examples 1-3 are shown in Table 1. The test methods for hydrophobicity, adhesion force, and wear resistance are as follows:

[0097] The hydrophobicity was tested using a contact angle measuring instrument (OCA20). At room temperature, 5 μL of distilled water was dropped onto the surface of the coatings prepared in Examples 1-4 and Comparative Examples 1-3, and its contact angle and rolling angle were measured. The results are shown in Table 1, where Figure 3 Figure 5 is a schematic diagram of the static contact angle of the superhydrophobic composite coating in Example 1.

[0098] The wear resistance was tested according to the reciprocating abrasion test method to detect the wear resistance of the superhydrophobic coating: A 1000-mesh sandpaper was fixed on the desktop as the wear surface, the coating was directly contacted with the sandpaper, and a 100-g weight was placed above the sample as the wear load. During the test, the sample was slowly pushed with a uniform force parallel to the sandpaper direction, so that the sample and the weight moved together, pushed from one end of the sandpaper to the other end (20 cm) and then returned, which was recorded as one cycle of wear, until the superhydrophobic performance of the coating failed. Figure 4 Figure 10 is a schematic diagram of the static contact angle of the coating in Example 1 after 200 cycles of friction, indicating that Example 1 still has high hydrophobicity after 200 friction cycles.

[0099] The adhesion force was tested according to the ASTM D3359 cross-cut method to detect the adhesion force of the superhydrophobic coating: The coating was cut into a grid pattern by a cross cutter; the surface impurities were gently swept away with a brush, the tape was placed parallel to the scribed grid in the middle, and the tape was smoothed by hand; the tape was torn off at an angle close to 60°, and the state of the cut part was checked. According to the peeling area, the adhesion of the coating was defined as grades 0B-5B. Grade 0B indicates extremely poor adhesion of the coating, and grade 5B indicates excellent adhesion of the coating. As can be seen from Table 1, the adhesion force of the superhydrophobic coating prepared in this example reaches grade 5B, and it still has superhydrophobicity after cross-cutting and peeling tests, as Figure 5 shown.

[0100] Table 1. Particle sizes of micro- and nano-silica and related performance tests in Examples 1-4 and Comparative Examples 1-3

[0101]

[0102] Table 1 shows that the coating prepared by in-situ growth of dual-sized silica boron nitride fillers has superhydrophobic properties and excellent wear resistance. However, coatings with only micron-sized silica of a single size or without silica growth cannot achieve superhydrophobic properties. At the same time, although the coating with only nano-sized silica can achieve superhydrophobic properties, due to the lack of protection by micron-sized silica, its superhydrophobic properties fail after 80 wear cycles. Therefore, the superhydrophobic coating prepared by growing dual-sized boron nitride particles can balance the superhydrophobic properties and wear resistance of the coating.

[0103] It should be understood that those of ordinary skill in the art can make improvements or transformations based on the above description, and all such improvements and transformations should fall within the protection scope of the appended claims of the present invention.

Claims

1. A method for preparing a durable super-hydrophobic composite filler, characterized in that: The steps include: 1) After dispersing the hydroxylated boron nitride particles in a first solvent, adding acid to adjust to acidity, then adding a silicon source to carry out a first composite reaction, in situ growing micron-sized SiO2 on the surface of the hydroxylated boron nitride, and obtaining primary BN@SiO2 composite particles; 2) The primary BN@SiO2 composite particles obtained in step 1) are dispersed in a second solvent, adjusted to alkalinity by adding alkali, and then a silicon source and a modifier are added to carry out a second composite reaction, and nano-SiO2 is in situ grown on the surface of the primary BN@SiO2 composite particles to obtain secondary BN@SiO2 composite particles, which are durable super-hydrophobic composite fillers.

2. The preparation method according to claim 1, characterized in that: In the step 1), adding acid to adjust the acidity means pH is 3.5-5.5; the reaction conditions are: temperature 20-80°C, time 1-3h; In the step 2), adding alkali to adjust the alkaline pH to 8-10.5; the reaction conditions are: temperature 20-80° C., time 1-3 h.

3. The preparation method according to claim 1, characterized in that: In the steps 1) and 2), the first solvent and the second solvent are independently selected from at least one of methanol, ethanol, propanol, isopropanol, and toluene, or a mixture of several thereof; the silicon source is independently selected from at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, and sodium silicate; In the step 2), the modifier is at least one of octyltrimethoxysilane, octyltriethoxysilane, octyltrichlorosilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, dodecyltrichlorosilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and hexadecyltrichlorosilane, or a mixture of several thereof.

4. The preparation method according to claim 1, characterized in that: In the step 1), the weight ratio of hydroxylated boron nitride to silicon source is (1-3):1; In the step 2), the weight ratio of the primary BN@SiO2 composite particles to the silicon source is (1-5):1, and the weight ratio of the primary BN@SiO2 composite particles to the modifier is (0.5-3):

1.

5. A durable super-hydrophobic composite filler prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the durable super-hydrophobic composite filler according to claim 5 in a durable super-hydrophobic composite coating.

7. A durable super-hydrophobic composite coating, characterized in that: Contains the durable super-hydrophobic composite filler as described in claim 5.

8. The durable super-hydrophobic composite coating according to claim 7, characterized in that: The composite coating comprises the durable super-hydrophobic composite filler according to claim 5, a resin, a curing agent, a third solvent and an additive; wherein: The weight ratio of the auxiliary agent, the curing agent and the durable super-hydrophobic composite filler to the resin is (0.01-0.15):(0.01-0.5):(0.01-0.5):1; the weight ratio of the resin to the third solvent is (0.005-0.5):1; The auxiliary agents include defoamers and leveling agents.

9. The durable super-hydrophobic composite coating according to claim 8, characterized in that: The resin is one or more of E12 epoxy resin, E42 epoxy resin, E44 epoxy resin, and E51 epoxy resin; The curing agent is at least one of diethylenetriamine, triethylenetetramine, diaminodiphenylmethane, m-phenylenediamine and dicyandiamide; The third solvent is at least one of ethyl acetate, toluene, xylene, butyl acetate, tetrahydrofuran, ethanol, cyclohexane, and acetone, or a mixture of several thereof; The defoaming agent is one or more of polydimethylsiloxane defoaming agent, ethylene glycol siloxane defoaming agent and polyether defoaming agent; The leveling agent is at least one of a polydimethylsiloxane leveling agent, an organic modified polydimethylsiloxane leveling agent and a polymethylphenylsiloxane leveling agent.

10. A durable super-hydrophobic composite coating, characterized in that: The durable super-hydrophobic composite coating according to any one of claims 7 to 9 is coated on a substrate and then cured by heating.

Citation Information

Patent Citations

  • Method for preparing superhydrophobic coating layer through composite of inorganic nano-particles with different average particle sizes

    CN105602297A

  • Preparation method of durable PDMS (polydimethylsiloxane) bionic super-hydrophobic membrane

    CN108299827A

  • Super-hydrophobic coating based on silicon resin fluorination modification

    CN109135565A

Cited By

  • A manufacturing process for aluminum alloy cables

    CN122563439A